Classification and characterization of a laboratory chicken rotavirus strain carrying G7P[35] neutralization antigens on the genotype 4 backbone gene configuration - Papp, Hajnalka; Marton, Szilvia; Farkas, Szilvia L.; Jakab, Ferenc; Martella, Vito; Malik, Yashpal S.; Palya, Vilmos; Bányai, Krisztián (Biologicals, 2014)
The laboratory rotavirus strain, BRS/115, has been used for more than two decades to monitor rotaviruses in specific pathogen free flocks of laying hens. However, the virus strain has not been characterized in detail. Therefore we aimed at the description of molecular features of BRS115 by using random primed reverse transcription-PCR of the genomic RNA followed by massive parallel sequencing using the semiconductor sequencing technology. Over 64,000 trimmed reads mapped to reference sequences obtained from GenBank. The strain classified into the species Rotavirus A and genotyped G7-P[35]-I4-R4-C4-M4-A16-N4-T4-E11-H4 according to guidelines of the Rotavirus Classification Working Group. Phylogenetic analysis identified shared features with chicken, turkey and pigeon origin rotaviruses. This study demonstrates the robustness of next generation sequencing in the characterization of reference virus materials used in specialized laboratories.